Model Latihan Waight Training Meningkatkan Akurasi Shooting 10 M Air Pistol Ditinjau Relaksasi Otogenik - Soemardiawan, Soemardiawan; Yundarwati, Susi; Marzuki, Ismail (Jurnal Porkes, 2025)
The low shooting accuracy of NTB athletes in the 10m air pistol event at the 2024 Aceh Medan PON, which only reached 75%, is the background to this research problem. This condition is strongly suspected to be caused by two factors: a lack of strength-based physical training (weight training), which results in weak arm muscle stability, and suboptimal management of cognitive anxiety that interferes with concentration. This study aims to test the effectiveness of an integrated training model that combines weight training to strengthen arm muscles with autogenic relaxation techniques to manage mental conditions in order to improve shooting accuracy. The method used is a quasi-experiment with a one-group pretest-posttest design on a sample of 60 Perbakin NTB shooting athletes. Accuracy data were collected through shooting tests before and after the intervention and analysed using a Paired Sample T-Test. The results of the analysis showed a significant increase in the average accuracy score of 6.88 points, from 539.43 to 546.32, with a significance value (p-value) of 0.000. The conclusion of the study proves that the integrated training model of weight training and autogenic relaxation is significantly effective in improving 10m air pistol shooting accuracy, emphasising the importance of a holistic approach that integrates physical and mental aspects in training programmes.